Energy transfer and color-tunable luminescence properties of Dy3+ and Eu3+ co-doped Na3Sc2(PO4)3 phosphors for near-UV LED-based warm white LEDs. (September 2018) - Vijayakumar, R.; Guo, Heng; Huang, Xiaoyong
Abstract: Dy 3+ singly doped and Dy 3+ /Eu 3+ co-doped Na3 Sc2 (PO4 )3 phosphors were synthesized by high temperature solid-state reaction and their photoluminescence properties were investigated. The prepared phosphors have a single phase trigonal structure of Na3 Sc2 (PO4 )3 and consist of micro-particles with an average particle size about 13.8 μm. Among all the Na3 Sc2 (PO4 )3 : x Dy 3+ samples, 5 mol% of Dy 3+ ions is found to be optimum concentration because it shows strongest emission intensity under 350 nm excitation. Under 350 nm excitation, the emission spectra of Na3 Sc2 (PO4 )3 :0.05Dy 3+, yEu 3+ phosphors are composed of several bands associated with the transitions of both Dy 3+ and Eu 3+ ions from the 4 F9/2 and 5 D0 excited states, respectively. It is noticed that integrated emission intensities of Dy 3+ ions were decreased with the increase of Eu 3+ ion concentration due to energy transfer from Dy 3+ to Eu 3+ ions. The Dexter theory and Reisfield's approximation were employed to analyze the energy transfer mechanism and it is found that the dipole-dipole interaction is responsible for energy transfer from Dy 3+ to Eu 3+ ions. Among the Na3 Sc2 (PO4 )3 :0.05Dy 3+, yEu 3+ phosphors, 5 mol% of Dy 3+ and 20 mol% of Eu 3+ are found to be optimum concentrations because it emits strong warm white light under 350 nm excitation. Further, the quantum efficiency, lifetime, energy transfer efficiency and correlated color temperature (CCT) values of the present phosphors were estimated and compared with the other reported phosphors. Graphical abstract: Tunable white emissions were achieved in Dy 3+ and Eu 3+ co-doped Na3 Sc2 (PO4 )3 phosphors for near-UV LED-based warm white LEDs. Highlights: Dy 3+ /Eu 3+ co-doped Na3 Sc2 (PO4 )3 phosphors were synthesized by solid-state reaction. Energy transfer efficiency from Dy 3+ to Eu 3+ reached 86%. Na3 Sc2 (PO4 )3 :0.05Dy 3+, 0.2Eu 3+ emitted warm white light under 350 nm excitation. Critical distance of energy transfer was found to be 8.09 Å.